PEMANFAATAN SENYAWA FLAVONOID DALAM EKSTRAK DAUN SAPUTANGAN (Maniltoa grandiflora (A.Gray) Scheff) SEBAGAI SENYAWA ANTIBAKTERI - Jhon Patar Sinurat; Reh Malem br Karo (JURNAL PENGMAS KESTRA (JPK), 2021)
The Saputangan's leaves extract contained flavonoid compounds which are proven based on the results of screening several flavonoid compound reagents. Flavonoid compounds were examined using FeCl3 to produce a black precipitate, mg metal and concentrated HCl produced an orange color, Alkaline reagents produced a brownish color, Lead acetate produced a cream color and ammonia vapor produced a yellow stain on the TLC plate. As 1000 g of saputangan leaves powder was macerated using methanol as a solvent, followed by the evaporation process in a rotary evaporator and over a water bath to obtain 100 mg of maserate. The maceration process was carried out for several days and the macerate was always checked through flavonoid screening. The flavonoid compounds in the Saputangan leaves could act as an antibacterial with medium strength which produces an average diameter of inhibition zone for S. aureus bacteria of 8.92 millimeters and E. coli bacteria of 9.42 millimeters. After the seminar, participants in the service activities understood that ornamental plants can be used as medicinal plants. In addition, participants also understood the procedures used in the antibacterial test on saputangan leaves.